Effects of Lentinan on Endothelial Cell Activity, Inflammatory Response, Endoplasmic Reticulum Stress, and Apoptosis in Sepsis - Yan Xu; Yeping Du (Advances in Polymer Technology)
The aim of this study is to explore the protective effects of lentinan on endoplasmic reticulum stress, inflammation, and apoptosis in sepsis endothelial cells. Firstly, lentinan was extracted, purified, and analyzed. When the concentration of lentinan was in the range of 0.04–4 μM, there was no obvious effect on the morphology of HUVECs. When the concentration reached 10 M, the cells were obviously contracted and necrotic. CCK-8 cell activity experiment showed that when the concentration of lentinan reached 4 μM, the cell activity decreased significantly (P<0.001), and it was in a dose-dependent manner. Then, the cells were divided into the control group (0 μM lentinan), sepsis group, sepsis + lentinan 1.2 μM group, and sepsis + lentinan 2 μM group. Enzyme-linked immunosorbent assay showed that lentinan could significantly reduce the expression of TNF-α, IL-1β, and IL-6 in sepsis endothelial cells (P<0.001). In addition, flow cytometry and TUNEL staining showed that compared with the control group, the apoptosis of cells in the sepsis group increased significantly (P<0.001), and lentinan could inhibit apoptosis (P<0.001). In terms of mechanism research, the mRNA and protein expression of endoplasmic reticulum stress-related protein in endothelial cells were detected by real-time fluorescent quantitative PCR (qPCR) and Western blotting, respectively. It was found that the expression of SIRT1, the upstream factors of endoplasmic reticulum stress in sepsis cells, was obviously inhibited (P<0.001), and the expression of CHOP, GRP78, IRE1α, and ATF6 was significantly increased (P<0.001), However, the pretreatment of lentinan could significantly reverse the above changes (P<0.001). Besides, lentinan could also reduce the expression of phosphorylated p65 protein (the activation marker of NF-κb) and iNOS. Conclusion. When sepsis occurs, lentinan can protect endothelial cells from ERS inflammation and apoptosis induced by sepsis. Thus, lentinan is expected to be a new target for the treatment of sepsis-induced endothelial damage.